ROLE OF NORMAL PERFUSION TIME ON FUNCTIONAL ENZYME ACTIVITIES AND PHYSIOLOGY OF INTERFIBRILLAR AND SUB-SARCOLEMMAL MITOCHONDRIA FROM ISOLATED RAT HEART - Kurian, Gino A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: Obvious lack of interfibrillar mitochondria (IFM) subpopulation in isolated mitochondria attributed to limitations in the isolation procedure. In this manuscript, we compared the functional activities of mitochondrial sub-populations namely, IFM and sub-sarcolemmal (SSM) mitochondria. Methods: IFM and SSM were obtained from isolated rat heart subjected to different perfusion time namely (minutes) 0.5,5,10,25,60 and 120 through Langendroff perfusion system. Results: Prolonged perfusion of isolated rat heart reduced oxidative phosphorylation capacity in both IFM and SSM, but were distinct among the sub-populations. However, mRNA expression level of ND4, CYT B and ATP 6 and resazurin activity was similar in both IFM and SSM. Conclusion: Even though overall function of myocardium is unchanged, mitochondrial sub- populations were distinct in electron transport chain activities, emphasizes the requirement to assess mitochondrial function as distinct subpopulation rather than whole entity. Â 